Exploring the Eschaton. The Lord’s Supper as a Cultural Technique Enabling Prefigurative Politics - Peter-Ben Smit (Yearbook for Ritual and Liturgical Studies, 2022)
Focusing on 1 Cor. 11, this article argues that the early Christian meal can be understood as a cultural technique that enables new knowledge and insight, specifically about the world to come. The argument takes its vantage point from an understanding of the early Christian meal as a form of social experimentation that engages in prefigurative practices, thereby anticipating the world to come. To explore the latter phenomenon, this article makes use of a body of theory concerning prefigurative politics, a field not commonly associated with the study of religion. However, it is shown that this body of theory is a useful tool for considering that the kind of knowledge regarding the world to come is made possible through the performance of the early Christian meal, understood as a cultural technique. In this manner, the present article aims to make contributions at the levels of both the theory regarding the study of the early Christian meal and insights into it.